Formulation and Evaluation of Fast Dissolving Oral Film of Sitagliptin Phosphate by Solvent Casting Method (International Journal of Ayurveda and Pharma Research, 2025)
The primary objective of this study was to develop sitagliptin phosphate oral films that dissolve quickly in order to treat diabetic mellitus. The solvent casting method was employed to make the sitagliptin phosphate films that dissolve quickly. Film forming polymers HPMC E 15 and HPMC E 50 cps were utilised, along with plasticisers PEG and propylene glycol. We tested the films for stability, in-vitro disintegration time, in-vitro dissolving test, drug content, thickness, folding endurance, percentage elongation, tensile strength, and scanning electron microscopy. The outcomes met or exceeded expectations. Formulation 3 had the quickest disintegration time at 20 seconds and the fastest drug release time at 3 minutes out of all the formulations. From the data shown above, it can be inferred that Sitagliptin phosphate fast-dissolving oral films have the potential to increase absorption by bypassing the first-pass effect and producing quick action.